Pengaruh Inovasi Produk dan Strategi Promosi terhadap Daya Saing Produk Ice Cream Mixue di Jakarta - Safitri, Finka; Purwatiningsih Purwatiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of product innovation and promotion strategies on the competitiveness of Ice Cream Mixue products in Jakarta. A quantitative approach was used with a survey method through the distribution of questionnaires to 97 respondents. The data analysis technique applied was multiple linear regression with the help of SPSS software version 21. The results of the partial test (t-test) showed that product innovation had a positive and significant influence on product competitiveness, with a calculated t value of 4.785 greater than the table t of 1.985 and a significance level of 0.000 < 0.05. The promotional strategy also showed a positive and significant influence, with a calculated t value of 3.376 > t table and a significance of 0.001 < 0.05. Simultaneously (F test), the two independent variables have a significant effect on product competitiveness, with the F value calculated at 38.398 > F table 3.09 and the significance of 0.000 < 0.05. A determination coefficient (R²) of 0.450 indicates that 45% of the variation in the competitiveness of Mixue's products is influenced by product innovation and promotional strategies. These findings confirm that the combination of sustainable innovation and effective promotional strategies is a key factor in increasing the competitiveness of products in a competitive market like Jakarta. This research makes a practical contribution to the development of marketing strategies and product innovation in the food and beverage industry.